Microscopic Examination of Acid-Resistant Bacils in Closed Contacts of Patients With Tuberculosis in The Working Area Of The UPTD Puskesmas Cilegon - Rahayu, Ayu Puji; Silviani, Yusianti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Tuberculosis is a contagious disease caused by Mycobacterium tuberculosis. The transmission of pulmonary TB occurs by the emission of droplets who are positive for the disease. Attempts were undertaken to examine interactions between cadres and the community. The patient's close contacts underwent microscopic inspection utilising the Ziehl Neelsen staining procedure. Between 2023 and October, a total of 360 cases of tuberculosis will be investigated using the ZN painting method. Among the close contacts of the 72 patients, 20% (6 individuals) will be identified as having tuberculosis. This study aimed to assess the outcomes of BTA microscopic examination conducted on close household contacts within the operating region of UPTD Puskesmas Cilegon in 2024. The research method employed a descriptive observational approach with a cross-sectional design. The study was carried out from 1 February to 9 March 2024 at the UPTD Puskesmas Cilegon. The sample technique employed is purposive sampling. The study findings revealed that out of the total number of respondents, 32 individuals reported having direct contact with individuals affected by tuberculosis. Among these respondents, 13 (40.6%) were male and 19 (59.4%) were female. Out of the 32 individuals who had close contact, one respondent (3.3%) tested positive for BTA when microscopic inspection was conducted. The proximity to the afflicted individual directly correlates with the heightened likelihood of transmission. Proximity between those who are infected and their close contacts can lead to the transmission of the infection, even when sharing the same sleeping space.